Studi kualitas air di area akuakultur Desa Eris Kabupaten Minahasa - Sinaga, Rohana; Undap, Suzanne L.; Kusen, Diane J.; Pangemanan, Novie P. L.; Mudeng, Joppy D.; Pangemanan, Jeannette (e-Journal BUDIDAYA PERAIRAN, 2021)
The aim of this study was to monitor the condition of water quality in the aquaculture area of fix net cage culture system (KJT) at Lake Tondano, Eris Village, Eris District, Minahasa Regency which included temperature, pH, DO, TDS, Turbidity, NO2, NH3, PO4  and sediment (N, Nitrogen and P, Phosphorus) in  a different time. This research was conducted from March to May 2021 using a survey method. The research activities consisted of direct measurements in the field (in situ) using a Horiba U-5000G instrument and laboratory analysis (ex situ) at the BTKLPP Class 1 Laboratory and the BARISTAND Laboratory in Manado for primary data. Primary data was carried out at 3 points, Point 1 represented around residential activities, Point 2 where the areas of cultivation activities, and Point 3 where outside of cultivation and settlement activities. Primary data was compared with secondary data i.e, publish articles and then processed in the STORET method. Data were evaluated to the water quality parameters standard according to the Indonesian Government Regulation number 22 of 2021. The results showed that the water temperature ranged between 26.3 - 28.07 0C, Turbidity (10.5 - 24.4 NTU), TDS (0.167 - 0.172 g/L), pH (3.79 - 7.84), DO (1.87 - 9.05 mg/L), NH3 (0.12 - 0.26 mg/L) , NO2 (0.001 - 0.064 mg/L), PO4 (0.2 mg/L - 1.67 mg/L). In the sediment samples, N was found in the  ranged of 0.20% - 0.26% and  P (0.48% - 2.69%). It can be concluded, the condition of water quality in the aquaculture area using KJT in Eris Village is categorized as class C (medium polluted) and N in the sediment criteria is moderate and the content of P in the sediment criteria is very low.